THE EXISTENCE ISLAMIC EDUCATION LEARNING FORMING STUDENTS’ LEVEL OF RELIGIOUS MATURITY - Ahmad Salamuddin; Munawar Rahmat; Fahrudin Fahrudin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
This research focused on analyzing the level of religious maturity of students at the junior high school level. The purpose of this study was to measure the level of student religiosity. To measure this, research was conducted using quantitative methods with 103 Muslim students as respondents using Probablity Sampling technique with stratified random sampling approach. The analysis test used was descriptive analysis, frequency distribution and normality test. The questionnaire used as many as 49 questions relating to the tendency towards religious maturity religiosity. This study found that the level of religious maturity of junior high school students is low by having a mean value of 175.59, median value 176, minimum value 135, maximum value 211, with a total value of 18,086. The implication of this study was to illustrate that islamic education learning can shape the religious maturity of students in junior high school, and the influence of religious activities carried out at school in shaping behavior that shows religious maturity.